Predictions and estimation of potential of rice residue management technologies in Punjab State of India - JADHAV, SWAPNAJA K; LANDE, SATISH DEVRAM; SINGH, K P; SHUKLA, LIVLEEN; SAHOO, P K; KHURA, TAPAN KUMAR; KUMAR, SANDEEP (The Indian Journal of Agricultural Sciences, 2025)
The agricultural data for the study was collected from 2010–11 to 2023–24 aimed to assess the potential of in situ and ex situ rice (Oryza sativa L.) residue management technologies in Punjab. The residue burning issue has intensified in the state’s highly mechanized rice–wheat (Triticum aestivum L.) cropping system (RWCS) due to an insufficient number of Crop Residue Management (CRM) machines. The actual number of CRM machineries required to cover the total area under the RWCS were estimated in order to manage rice residues of the state completely. Based on maturity of prominent rice varieties, predicted timeframe is of only 10 days to operate CRM machines effectively. Potential area coverage of CRM machineries was estimated for selected time frames (5, 10, 15, 20, 25 and 30 days) and the possible combinations of CRM machinery were suggested based on operational time window available for both timely and delayed scenarios between rice and wheat crops. Feasibility of Super Straw management System (SMS) followed by both Happy Seeder and Super Seeder to cover total rice cultivated area were analysed and predicted. It revealed that the time window of 15, 20, 25 and 30 days to operate Happy Seeders in the state can cover only 13.22%, 27.23%, 34.03% and 40.84% of the cultivable area while Super Seeder can cover 17.17%, 34.35%, 42.94% and 51.51% area, respectively. Additionally, the ex situ management potential for 2024–25 was estimated at a gross residue of 21.98 MT, surplus residue of 5.71 MT, and an annual power generation potential of 994.4 MW with a CGAR of 2.04%.